Анализа корелације нивоа сретног sTREM-1 и sHLA-DR у серуму са прогнозом пацијената са атријалном фибрилацијом: Серумски sTREM-1 и sHLA-DR у прогнози атријалне фибрилације - Guo, Anqi; Zhu, Jiayi; Zhao, Liqun (Journal of Medical Biochemistry, 2026)
[Objective] To observe the expression levels of serum soluble Triggering Receptor Expressed on Myeloid cells-1 (sTREM-1) and serum soluble Human Leukocyte Antigen-DR (sHLA-DR) in patients with atrial fibrillation (AF) and their clinical significance.[Methods] 136 patients with atrial fibrillation who were admitted from April 2023 to September 2025 were selected as the research group, and 100 healthy individuals who underwent physical examinations during the same period were selected as the control group. The serum levels of sTREM-1 and sHLA-DR were detected by ELISA, and the serum levels of interleukin-6 (IL-6) and C-reactive protein (CRP) were measured by an automatic biochemical analyzer.[Results] The study group exhibited elevated blood levels of sTREM-1 and sHLA-DR in comparison to the control group (P < 0.05). Regarding patient age, sex, type of atrial fibrillation, and EHRA classification, there were statistically significant variations in the blood levels of sTREM-1 and sHLA-DR between the study group and the control group (P < 0.05). The study group had greater levels of CRP and serum IL-6 than the control group (P < 0.05). The expression levels of sTREM-1 and sHLA-DR in the serum were shown to be favorably linked with those of IL-6 and CRP (P < 0.05) using Pearson correlation analysis. Serum levels of the inflammatory markers IL-6 and CRP, as well as sTREM-1 and sHLA-DR, were found to be strongly associated with AF, according to the results of the logistic regression analysis.[Conclusion] Serum levels of sTREM-1 and sHLA-DR are increased in patients with atrial fibrillation, which may be related to the onset and progression of AF. Clinically, these can be considered relevant biological indicators for monitoring the condition of AF.